Facilitating Positive Spillover Effects: New Insights From a Mixed-Methods Approach Exploring Factors Enabling People to Live More Sustainable Lifestyles - Elf, Patrick; Gatersleben, Birgitta; Christie, Ian (Frontiers in Psychology, 2019)
Positive spillover occurs when changes in one behaviour influence changes in subsequent behaviours. Evidence for such spillover and an understanding of when and how it may occur is still limited. This paper presents findings of a one year longitudinal behaviour change project led by a commercial retailer in the UK & Ireland to examine behaviour change and potential spillover of pro-environmental behaviour, and how this may be associated with changes in environmental identity and perceptions of ease and affordability as well as perceptions of how participation in the project has helped support behaviour change. We draw on both quantitative and qualitative. Study 1 examines quantitative data from the experimental and a matched control group. Study 2 reports qualitative findings from a follow up interview study with participants of the experimental group. As expected, we found significant changes in reported pro-environmental behaviour and identity in the experimental group as well as some indications of behavioural spillover. These changes were not significantly associated with changes in environmental identity. The interviews suggested that group dynamics played an important role in facilitating a sense of efficacy and promote sustained behaviour change and spillover. Moreover, the support by a trusted entity was deemed to be of crucial importance.